Influence of Work Environment and Work Motivation to Performance Employee - Krisinta, Lerry (JEMBA: Jurnal Ekonomi Pembangunan, Manajemen & Bisnis, Akuntansi, 2023)
This research aims to provide an empirical explanation regarding the influence of the work environment and work motivation on employee performance at PT. Parwata Rimba in South Barito Regency. The research method used in this research is Quantitative Research using Descriptive Statistics techniques and Multiple Linear Regression analysis. The population and sample in this study were employees of PT. Parwata Rimba totaling 40 respondents using Saturated Sampling or Census techniques. The collected data was analyzed using the SPSS version 25 program. The research results showed that: a) the work environment did not have a significant effect on employee performance, b) work motivation did not have a significant effect on employee performance, and c) simultaneously the work environment and work motivation had an effect. positive and significant on employee performance.